Question
upstudy study bank question image url

Solve the equation. \( (6 x-1)^{2 / 3}=x^{1 / 3} \) The solution set is \( \{ \) (Simplify your answer. Type an integer complex numbers in terms of \( i \) )

Ask by Zimmerman Medina. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solutions are \( x = \frac{1}{9} \) and \( x = \frac{1}{4} \).

Solution

Solve the equation \( (6x-1)^{2/3}=x^{1/3} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\left(6x-1\right)^{\frac{2}{3}}=x^{\frac{1}{3}}\) - step1: Raise both sides to the \(3\)-th power\(:\) \(\left(\left(6x-1\right)^{\frac{2}{3}}\right)^{3}=\left(x^{\frac{1}{3}}\right)^{3}\) - step2: Evaluate the power: \(\left(6x-1\right)^{2}=x\) - step3: Expand the expression: \(36x^{2}-12x+1=x\) - step4: Move the expression to the left side: \(36x^{2}-12x+1-x=0\) - step5: Subtract the terms: \(36x^{2}-13x+1=0\) - step6: Factor the expression: \(\left(4x-1\right)\left(9x-1\right)=0\) - step7: Separate into possible cases: \(\begin{align}&4x-1=0\\&9x-1=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=\frac{1}{4}\\&x=\frac{1}{9}\end{align}\) - step9: Rewrite: \(x_{1}=\frac{1}{9},x_{2}=\frac{1}{4}\) The solutions to the equation \( (6x-1)^{2/3}=x^{1/3} \) are \( x = \frac{1}{9} \) and \( x = \frac{1}{4} \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To solve the equation \( (6x - 1)^{2/3} = x^{1/3} \), we can start by raising both sides to the power of \( 3 \) to eliminate the fractional exponents: \[ (6x - 1)^{2} = x \] Expanding the left side, we have: \[ (6x - 1)(6x - 1) = x \] This simplifies to: \[ 36x^2 - 12x + 1 = x \] Rearranging gives: \[ 36x^2 - 13x + 1 = 0 \] Now we can use the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \) where \( a = 36 \), \( b = -13 \), and \( c = 1 \): Calculating the discriminant: \[ b^2 - 4ac = (-13)^2 - 4(36)(1) = 169 - 144 = 25 \] Then we find the roots: \[ x = \frac{13 \pm \sqrt{25}}{2 \cdot 36} = \frac{13 \pm 5}{72} \] This gives us two solutions: 1. \( x = \frac{18}{72} = \frac{1}{4} \) 2. \( x = \frac{8}{72} = \frac{1}{9} \) Next, we need to verify if these solutions satisfy the original equation, especially since raising to an even power can introduce extraneous solutions. For \( x = \frac{1}{4} \): \[ (6(\frac{1}{4}) - 1)^{2/3} = (1.5)^{2/3} \quad \text{and} \quad (\frac{1}{4})^{1/3} = (0.25)^{1/3} \] Evaluate \( 6(\frac{1}{4}) - 1 = 1.5 \): \[ (1.5)^{2/3} = \sqrt[3]{(1.5)^2} = \sqrt[3]{2.25} \] For \( x = \frac{1}{9} \): \[ (6(\frac{1}{9}) - 1)^{2/3} = (-\frac{1}{3})^{2/3} = \frac{1}{\sqrt[3]{9}} \quad \text{and} \quad (\frac{1}{9})^{1/3} = \frac{1}{3} \] Substituting back validates that \( x = \frac{1}{4} \) fits while \( x = \frac{1}{9} \) does not yield a valid output due to extraneous roots. Thus, the solution set is: \{ \(\frac{1}{4}\) \}

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy